Linguistic Identities in the Arab Gulf States : Waves of Change. - Hopkyns, Sarah; Zoghbor, Wafa. (Milton : Taylor & Francis Group, 2022)
Combining empirical and theoretical approaches from a range of disciplines, Linguistic Identities in the Arab Gulf States examines current issues surrounding language and identity in the Arab Gulf States.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books